Karakter Keteladanan Profil Pelajar Rahmatan Lil ’Alamin (PPRA) Dalam Program Merdeka Belajar Perspektif Surat Al-Mumtahanah Ayat 4 - Izzan, Ahmad; Iqbal, Muhammad (STAI Al-Musaddadiyah Garut, 2023)
The profile of Rahmatan Lil ‘Alamin students embodies strong national commitment, tolerance towards others, principles rejecting physical and verbal violence, and respect for tradition. PPRA (Preventive Action, Response, and Analysis) emphasizes exemplary values aimed at mitigating the decline in student morals. Surat Al-Mumtahanah verse 4 exemplifies Prophet Ibrahim's commitment to faith despite challenges. This study aims to describe the exemplary character of PPRA in the context of the